2018
DOI: 10.1088/1741-2552/aaac36
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing functional segregation across brain rhythms as a means to detect EEG oscillatory multiplexing during music listening

Abstract: Complying with the contemporary trends towards a multi-scale examination of the brain network organization, our approach specifies the form of neural coordination among rhythms during music listening. Considering its computational efficiency, and in conjunction with the flexibility of in situ electroencephalography, it may lead to novel assistive tools for real-life applications.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 70 publications
0
15
0
Order By: Relevance
“…is is actually a process of rhythm detection and beat tracking [5]. In the process of cluster center update, the data objects with the smallest distance to the sample in the cluster were selected as the cluster centers, and then the other data objects were divided into the corresponding clusters by the minimum distance so as to realize the clustering.…”
Section: Introductionmentioning
confidence: 99%
“…is is actually a process of rhythm detection and beat tracking [5]. In the process of cluster center update, the data objects with the smallest distance to the sample in the cluster were selected as the cluster centers, and then the other data objects were divided into the corresponding clusters by the minimum distance so as to realize the clustering.…”
Section: Introductionmentioning
confidence: 99%
“…Starting with selectivity, the delineation of a subgraph B of interest, in which the spectral analysis will put emphasis on, is performed using a graph-clustering algorithm in the way that it was recently introduced for sensor-selection in covariance-based decoding of MI [44]. The particular algorithm, known as Dominant-Set (DS) algorithm [49], [50], identifies the most coherent group of nodes in a given connectivity graph. The Appendix provides a short description of its adaptation towards discriminative learning in the setting of multichannel EEG signals.…”
Section: Graph Slepians For Eeg Activity From Cortical Networkmentioning
confidence: 99%
“…However studies have shown that simply listening to or tapping along with the rhythmic structure of music entrains the brain's low-frequency oscillations (Lakatos et al, 2008;Besle et al, 2011). For example, passive listening to musical sequences induces changes within alpha (Bridwell et al, 2017) and increases coupling between delta and high beta frequency ranges (Adamos et al, 2018). Word lists that are sung rather than spoken increase alpha coherence in bilateral frontal areas (Thaut et al, 2005) known to support learning-related processes (Sato et al, 2018).…”
Section: Entrainment Of Neural Oscillationsmentioning
confidence: 99%